Identification of non-value adding activities in precast concrete production to achieve low-carbon production - Wu, Peng; Feng, Y. (EarthScan, 2014)
The lean production philosophy originates from the Toyota Production System and has been applied in the construction industry for decades to eliminate wastes and improve efficiency. Many studies have been completed on the application of the lean philosophy to meet the challenges of sustainable development in precast concrete factories. Many non-value adding activities have been identified in both site layout and supply chain for precast concrete manufacturers. However, the production process should not be overlooked from a lifecycle perspective. This study adopts a weighted factor model comprising of 17 precasters in the Singapore precast concrete industry. The production process is investigated using the weighted factor model. The results indicate that there are many non-value adding activities in the production practices that contribute to an increase in the carbon emissions level. Large inventory level, wastage of raw materials and inexperienced employees seem to be the most important non-value adding activities. The analysis provides good practice guidance and can be used as a checklist for precasters to identify the non-value adding activities in the precast concrete production process to achieve low-carbon production. The results will also be useful for regulatory agencies to provide recommendations for precast concrete manufacturers to reduce carbon emissions.